2009
DOI: 10.1089/ars.2008.2218
|View full text |Cite
|
Sign up to set email alerts
|

Going Ape as an Approach to Cancer Therapeutics

Abstract: The DNA base excision repair (BER) pathway repairs alkylation and oxidative DNA damage caused by endogenous and exogenous agents, including chemotherapeutic agents. Upon removal of the damaged base AP endonuclease 1 (Ape1), a critical component of the pathway cleaves the abasic site to facilitate repair. Ape1 is a multifunctional protein which plays a role not only in DNA repair but it also functions as a reduction-oxidation factor, known as Ref-1 in the literature, to increase the DNA binding ability of sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
111
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(115 citation statements)
references
References 136 publications
(246 reference statements)
4
111
0
Order By: Relevance
“…Only the highest concentration (50 μM) shows a statistically significant (21%) increase in damage over the control, whereas DOPA and MYR induce a 48% and 50% increase in damage, respectively, at 10-fold lower concentrations. Interestingly, two studies have reported no effect on cell survival when using NCA with DNA damaging agents (43,45). Our results suggest that NCA may have some effect on cells, but both DOPA and MYR are far more potent.…”
Section: Resultsmentioning
confidence: 49%
“…Only the highest concentration (50 μM) shows a statistically significant (21%) increase in damage over the control, whereas DOPA and MYR induce a 48% and 50% increase in damage, respectively, at 10-fold lower concentrations. Interestingly, two studies have reported no effect on cell survival when using NCA with DNA damaging agents (43,45). Our results suggest that NCA may have some effect on cells, but both DOPA and MYR are far more potent.…”
Section: Resultsmentioning
confidence: 49%
“…Elevated levels of Ape1 have been linked to resistance to chemotherapy and poor prognosis (Bapat et al, 2008), and inhibition of Ape1 DNA repair activity and/ or its redox activity may be a promising avenue to develop novel cancer therapeutics and chemoprevention. Therefore, we speculate that inhibition of Ape1 redox activity may enhance cisplatin sensitivity to kill lung cancer with cytoplasmic Ape1.…”
Section: Discussionmentioning
confidence: 99%
“…These genotoxic agents are administered to cancer patients in combination, and in some cases with small molecule inhibitors to block DNA repair pathways with the aim of sensitizing cancer cells towards the chemotherapeutic regimens [4][5][6][7][8]. Although these molecules are hydrophilic in nature, it was commonly accepted that they diffuse into cells.…”
Section: Introductionmentioning
confidence: 99%